Trends and evolution in Islamic social finance research: A comprehensive bibliometric study - Sudarsono, Heri; Nugrohowati, Rindang Nuri Isnaini; Mifrahi, Mustika Noor; Tumewang, Yunice Karina; Fitriyani, Yeny; Lidasan, Mussolini Sinsuat (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study provides a comprehensive overview of the current state of Islamic social finance literature using VOSviewer analysis to identify key themes, trends, and emerging areas in this field.Methodology – A bibliometric analysis was conducted using VOSviewer to map and visualize key concepts and emerging topics in the Islamic social finance literature. The analysis focuses on the term